The Influence of Work Environment and Work discipline on the Performance of Employees of PDAM Madiun Regency - Puspita Sari, Wanodya; Pradana, Wina Driyan (Journal of Agriprecision & Social Impact, 2024)
Using purposive sampling, we obtained a sample size of 110 respondents. The research results show that the work environment has a positive and significant effect on the performance of PDAM Madiun Regency employees, with an original sample value of 0.259 and a T statistic of 2.658 (>1.96). Work discipline has a positive and significant effect on the performance of PDAM Madiun Regency employees, with an original sample value of 0.521 and a T statistic of 5.21 (>1.96). Simultaneously, the work environment and work discipline have a positive and significant effect on the performance of PDAM Regency employees, with a P value of 0.000 (<0.05). From this research, it can be concluded that employee performance will increase when a company's work environment and discipline are good.